Reduce your engineering drawing errors : preventing the most common mistakes - Hanifan, Ronald; Hanifan, Ronald (New York, NY : Momentum Press, 2010)
In this book, I will discuss only the most common errors that appear on engineering drawings and the basic usage and understanding of the most frequently used drawings. All drawings will contain errors, but if you can eliminate many of those errors before the engineering design checker or your supervisor reviews your drawing, it will go through much easier. Your reputation is at stake! Your supervisor and the engineering design checker will see everyone's work and know their errors. They know your weak areas and who produces good work and who doesn't. It is helpful to know what they look for--or should be looking for.
Chapter 1. First step is done, design is complete. -- Chapter 2. Understand the data that you have placed on the drawing -- The most common error: dimensions originating from the center of a feature -- Other frequent errors. -- Chapter 3. Dimensioning and tolerancing errors. Chapter 4. Drawing types: select the proper drawing for your action -- Drawing statements -- Mono-detail or multi-detail drawing -- Detail drawing -- Matched set drawing -- Assembly drawing -- Inseparable assembly -- Detail assembly -- Altered item drawing to alter an existing item -- Printed wiring board detail drawing -- Control drawings -- Vendor item drawing -- Procurement control drawing -- Envelope drawing -- Source control drawing -- Associated lists -- Drawing notes -- Isometric views (value questionable) -- Chapter 5. Electrical reference designations -- How assigned -- Which items receive a reference designation -- Reference designation starts -- Units, sets, and nomenclature -- Assigning reference designation -- Cable assemblies -- Marking -- Connector, wiring side -- Partial reference designations -- Chapter 7. Delivery of your drawings (technical data package) -- Vendor prints -- Missing drawings -- Undisclosed data -- Delivery of digital data and models -- Chapter 8. The checker: what he will look for -- Chapter 9. Other information -- Definition of common terms.
Includes index.
Keywords: ENGINEERING DRAWINGS